The Role Rotation and Training On Employee Performance - Si Toro, Munawir; Syarifuddin, Andi; Hasma; Prasetyo, Agung (Journal of Management, 2023)
The purpose of this study is to assess and analyze staff performance at PT. Banjar Industrial Borneo Facilities objectively in relation to workload, training, and personnel rotation. Given PT. Banjar Industrial Borneo Facilities' particular situation and the difficulties it faces in managing its human resources, the research site in Banjar Regency was selected. In order to provide a complete picture of the impact of research factors on employee performance, census methodologies were used to include all 48 employees of PT Sarana Borneo Industri Banjar as respondents in this study. The information utilized includes both quantitative information—obtained via government reports and personnel counts—and qualitative information—obtained from speaking with relevant authorities. Documentation and questionnaires were used in the data gathering process. The questionnaire measured respondents' attitudes, opinions, and perceptions on staff rotation, workload, and training using a Likert scale. Workload management, staff rotation, and efficient training.